The Effect of Professionalism and Competence on The Performance of Regional Representatives Council - Kadarisman, Muh. (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2012)
The research aims to analyze the effect of Bogor Regency’s Regional Representatives Council members’ professionalism and competence on their performance. The research uses a quantitative approach and employs the descriptive method. Findings suggest that Bogor Regency’s Regional Representatives Council members’ professionalism and competence directly influence their performance in a positive and significant manner. Result of this research also show that with increasing competence of members of parliament, it will has an impact on improving the performance of legislators—that is because they are a higher priority on support capabilities are more conducive to understanding the rules and duties of their employment. Study recommends that include other factors besides the professionalism and competence of members of parliament in order to measure performance improvement legislators.